You Can’t Hear “Aeneas” without Thinking of Rome. - KOCHENASH, MICHAEL (Journal of Biblical Literature)
The long-standing connection between the Trojan Aeneas and Rome was advertised throughout the empire in various ways, but scholars rarely draw from this cultural capital when interpreting Acts 9:32–35, an account of Peter healing a man named Aeneas. They often assume both that Aeneas is well attested as a personal name during the first and second centuries of the Common Era (it is not) and that Luke inherited this name from a source (which is possible but insufficient). Acts 9:31 is a summary statement on the progress of the church in Judea, Samaria, and Galilee. Readers who recall Jesus’s commission in Acts 1:8 will wonder about “the end of the earth.” Given the proximity of the Aeneas pericope to Luke’s summary statement and the fact that the narrative of Acts ends in Rome, I argue that the story of Aeneas can be read as a literary signpost for Rome (comparable to Luke 9:51–53 and Jerusalem). Luke’s use of “Aeneas” as a structuring device works in tandem with “Joppa” in Acts 9:36–43, which signals the inclusion of gentiles by evoking the thought world of Jonah. The balance of Luke’s narrative consists of negotiating and expanding the gentile mission and progressively moving toward the city of Rome. In this way, two proper nouns function as metonymic signposts to foreshadow the direction of the narrative, in both ethnic and geographic terms.